DESAIN PEMBERDAYAAN UMKM BERBASIS ONE VILLAGE ONE PRODUCT SEBAGAI GERAKAN EKONOMI BERNILAI KEARIFAN LOKAL: ONE VILLAGE ONE PRODUCT-BASED SMES EMPOWERMENT DESIGN AS ECONOMIC MOVEMENT WITH LOCAL WISDOM VALUE - Arina Hidayati (Jurnal Utilitas, 2020)
OVOP is a program with the following missions: producing globalizing local product, producing product based on self-creativity and ability, and being able to develop human resource competency. OVOP program is expected to realize the superior product in each of businesses belonging to SMEs in Indonesia; thus, it is expected to realize an independent economy. This research aimed to describe the OVOP-based SMEs empowerment design as economic movement with local wisdom value. The research method employed was the qualitative one, with case study design. This research took place in Batik Bagus Warna Alam SME in Denasri Village. Techniques of collecting data used were interview, observation, and document study. Technique of analyzing data used was Spradley’s domain analysis. Data validation test in this study was conducted using data credibility test. Data credibility test was carried out using triangulation technique. The result of research showed that OVOP-based SMEs empowerment in Batik Bagus Warna Alam SME in Denasri Village was conducted in some stages: (1) choosing product with local typical characteristic, (2) education, training, and expert mentor corresponding to each area of SMEs, (3) implementing product monitoring, and (4) mapping local potency based on local wisdom values. However, in practice SMEs empowerment in Batang Regency has not been based on local wisdom values.